Realization of the TOW-THOMAS Biquad Active Filter - Manandhar, Sagun (KEC Journal of Science and Engineering, 2023)
The Tow-Thomas Biquad Circuit provides the filter designers with a valuable building block for building higher order active filters. It is a flexible circuit structure in which the transfer function properties are easily manipulated by modifying the passive RC elements that connect the operational amplifiers. It can be easily defined in its low-pass and bandpass operations. Above all, we can easily fabricate the possible filters inside a single chip with very slight modification of the standard Tow-Thomas Circuit.